Changes in Dental Benefits and Use of Emergency Departments for Nontraumatic Dental Conditions in Massachusetts. (September 2020) - Ranade, Ashwini; Young, Gary; Garcia, Raul; Griffith, John; Singhal, Astha; McGuire, Jean
Objectives: Research examining the effect of changes in Medicaid dental benefits on emergency department (ED) use for dental conditions has had mixed results. We examined the effect of changes in Medicaid dental benefits on ED use for nontraumatic dental conditions (NTDCs) among adults in Massachusetts before and after Medicaid dental benefits for adults were eliminated (July 2010) and partially restored (January 2013). Methods: We used 2009-2013 data from the Massachusetts All-Payer Claims Database. The study population included Medicaid enrollees aged ≥21 who made a visit to the ED for an NTDC that was paid for by Medicaid during the study period. We used an interrupted time-series study design and segmented regression model to assess the effect of the policy changes on ED use for NTDCs. We also conducted a subanalysis by patient age, sex, and geographic location. Results: During the study period, 21 731 Medicaid enrollees aged ≥21 made 35 660 NTDC ED visits. Eliminating comprehensive dental benefits led to a significant increase in the use of EDs for NTDCs. This increase occurred over time (11% increase at 15 months after elimination of comprehensive dental benefits; estimate, 0.64 [95% CI, 0.07-1.21]; P = .03) rather than immediately after the policy change took effect. The partial restoration of certain dental benefits led to a significant decrease in the rate of ED visits for NTDCs over time (15.7% decrease at 5 months after partial restoration of certain dental benefits; estimate, –0.97 [95% CI, –1.83 to –0.11]; P = .03). Conclusion: Strengthening dental coverage policies for adult Medicaid enrollees could decrease their reliance on EDs for NTDCs.